Fiber yarns/CNT hierarchical structures as thermoelectric generators. (2017) - Tzounis, L.; Gravalidis, C.; Vassiliadou, S.; Logothetidis, S.
Abstract: Due to the increasing demand of alternative energy resources, considerable research interest has been devoted for the development of new thermoelectric materials. Thermoelectric materials are potential candidates for harvesting green energy, due to their ability to generate voltage upon exposure to a temperature difference. Herein, an interesting material used for engineering applications; glass fibers (GFs), were chemically grafted with single- and multi-wall carbon nanotubes (MWCNTs, SWCNTs) and utilized as flexible thermoelectric power generators. CNT-networks were covalently attached onto the surface of intrinsically insulating glass fiber yarns (GF-yarns) following a dip-coating deposition process. The fiber/CNT functional hierarchical yarns showed a maximum power factor ( PF ) of ∼109.8 μW/mK -2 (GF-SWCNT). The PF values were found in general to be increased with the increased amount of CNTs grafted onto the fiber surface. The idea of fiber/CNT structures for thermal energy harvesting could be further applied to several consumer applications, such as to smart textiles for wearable applications with the potential of harvesting thermal energy.